2017
DOI: 10.1128/msystems.00162-16
|View full text |Cite
|
Sign up to set email alerts
|

Balance Trees Reveal Microbial Niche Differentiation

Abstract: By explicitly accounting for the compositional nature of 16S rRNA gene data through the concept of balances, balance trees yield novel biological insights into niche differentiation. The software to perform this analysis is available under an open-source license and can be obtained at https://github.com/biocore/gneiss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
277
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(280 citation statements)
references
References 27 publications
3
277
0
Order By: Relevance
“…After removing Cyanobacteria, there is no apparent difference in diversity or evenness. Removing cyanobacterial reads does not remove their influence on other OTUs, because of the dependence structure of compositional data (Gloor and Reid, 2016;Morton et al, 2017). However, even if removing Cyanobacteria creates a bias in the rest of the data, the same bias is introduced in both bloom and non-bloom samples alike, so the comparison should remain valid.…”
Section: Discussionmentioning
confidence: 99%
“…After removing Cyanobacteria, there is no apparent difference in diversity or evenness. Removing cyanobacterial reads does not remove their influence on other OTUs, because of the dependence structure of compositional data (Gloor and Reid, 2016;Morton et al, 2017). However, even if removing Cyanobacteria creates a bias in the rest of the data, the same bias is introduced in both bloom and non-bloom samples alike, so the comparison should remain valid.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are statistically more appropriate for many analyses (Morton et al. ), and robust to different levels of ability to quantify co‐occurring compounds.…”
Section: Methodsmentioning
confidence: 99%
“…We elected to use absolute concentrations because we felt that they were a more direct reflection of the collected data, possibly more ecologically meaningful for interactions with mutualists and antagonists , Barlow et al 2017, and more relevant to future bioassays that test activity of specific compounds. In addition, they are statistically more appropriate for many analyses (Morton et al 2017), and robust to different levels of ability to quantify co-occurring compounds.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In the event that these primer sets miss a few essential taxa, databases such as probeBase or SILVA database provide the ability to design sequencing primers (Klindworth et al, 2013). Knowledge regarding the choice of primers for detection of archaea, fungi and viruses may be retrieved from previously published papers, for archaea: Fischer, Gullert, Neulinger, Streit, and Schmitz (2016) which emphasizes the fact that the results of a microbial investigation provide an overview or image of a microbial community without necessarily providing full accuracy (Morton et al, 2017). A recent study reported on the relative abundance of bacterial taxa from the phylum to the genus level and revealed high reproducibility when the same research centre repeated the analyses (i.e., high intra-centre reproducibility), while low reproducibility of results occurred when the same sample was processed in different laboratories (i.e., low intercentre reproducibility), mainly due to the use of different PCR primers (Hiergeist, Reischl, & Gessner, 2016).…”
Section: "Who Is There?": Profiling the Bacterial Taxa Of A Communitymentioning
confidence: 99%